2020
DOI: 10.1007/s13238-019-00684-8
|View full text |Cite
|
Sign up to set email alerts
|

Washed microbiota transplantation vs. manual fecal microbiota transplantation: clinical findings, animal studies and in vitro screening

Abstract: Fecal microbiota transplantation (FMT) by manual preparation has been applied to treat diseases for thousands of years. However, this method still endures safety risks and challenges the psychological endurance and acceptance of doctors, patients and donors. Population evidence showed the washed microbiota preparation with microfiltration based on an automatic purification system followed by repeated centrifugation plus suspension for three times significantly reduced FMT-related adverse events. This washing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
178
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 182 publications
(201 citation statements)
references
References 63 publications
1
178
1
4
Order By: Relevance
“…In addition, prolonged eradication therapy for H. pylori infection also leads to dysbiosis of the intestinal microbiota and increases the expression of resistance genes, which may further induce various diseases [ 12 , 15 , 16 , 29 ]. However, with the emergence of WMT and fecal suspension capsules, the safety and convenience of WMT have been significantly improved [ 23 , 30 ]. It is notable that WMT may be used for refractory H. pylori infection (defined as those who have failed the first eradication treatment or with recurrence of H. pylori infection).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, prolonged eradication therapy for H. pylori infection also leads to dysbiosis of the intestinal microbiota and increases the expression of resistance genes, which may further induce various diseases [ 12 , 15 , 16 , 29 ]. However, with the emergence of WMT and fecal suspension capsules, the safety and convenience of WMT have been significantly improved [ 23 , 30 ]. It is notable that WMT may be used for refractory H. pylori infection (defined as those who have failed the first eradication treatment or with recurrence of H. pylori infection).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that FMT is efficacious for the treatment of a variety of gut microbiota-related diseases, including digestive system and nondigestive system diseases [ 19 22 ]. FMT on the basis of washed microbiota preparation, known as washed microbiota transplantation (WMT), has been proven to decrease adverse events caused by traditional fecal suspension preparation and greatly improve the efficacy [ 23 , 24 ]. We speculate that WMT can also be used, alone or in combination with currently recommended regimens, to eradicate H. pylori infection, by restoring the gut microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ott et al 54 used sterile-filtered stools from healthy donors for patients with symptomatic chronic-relapsing C. difficile infection; they showed that these methods effectively eliminated symptoms in patients, whereas fecal microbiota did not. In addition, Zhang et al 55 reported that transplantation of washed microbiota may be safer and more easily controlled approach, compared with FMT prepared manually. The previous and ongoing studies (both preclinical and clinical) will serve to advance the use of FMT in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Washed microbiota transplantation (WMT) is an updated version of FMT developed on the basis of washed bacteria preparation, which has signi cant effects on the improvement of microbiota dysbiosis. 8 In this clinical trial protocol, WMT will be employed to treat GMD. We design this clinical trial protocol to explore the clinical e cacy and safety of WMT on COVID-19 suspected with GMD.…”
Section: Introductionmentioning
confidence: 99%